Thinning films and tribological interfaces : proceedings of the 26th Leeds-Lyon Symposium on Tribology held in the Institute of Tribology, School of Mechanical Engineering, the University of Leeds, UK 14th-17th September, 1999 /: proceedings of the 26th Leeds-Lyon Symposium on Tribology held in the Institute of Tribology, School of Mechanical Engineering, the University of Leeds, UK 14th-17th September, 1999. (2000) - Unknown
No abstract available